2000
DOI: 10.1021/es9908725
|View full text |Cite
|
Sign up to set email alerts
|

Drive-by Motor Vehicle Emissions:  Immediate Feedback in Reducing Air Pollution

Abstract: Using input from the public, a new type of vehicle emissions information system has been developed which utilizes an innovative variable message sign to display individual vehicle emissions information to passing drivers. Called the Smart Sign, the system merged highway messaging and on-road vehicle emissions sensing into a costeffective public information system. The Smart Sign used a combination of words, colors, and graphics to connect with its audience. During its operational test period the system proved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…However, even some simple measurements could assist in reducing the uncertainties. For example, remote‐sensing measurements such as those described by Bishop et al [2000] could assist in estimating the fraction of superemitters, contributing to understanding of gaseous emissions in addition to PM. However, the interpretation of these measurements needs refinement in order to attribute particulate matter to different vehicle types.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, even some simple measurements could assist in reducing the uncertainties. For example, remote‐sensing measurements such as those described by Bishop et al [2000] could assist in estimating the fraction of superemitters, contributing to understanding of gaseous emissions in addition to PM. However, the interpretation of these measurements needs refinement in order to attribute particulate matter to different vehicle types.…”
Section: Resultsmentioning
confidence: 99%
“… Lawson [1993] reported that 10% of the light‐duty vehicle fleet in California emitted 60 percent of the carbon monoxide, implying that the high‐emitting fraction averaged 13 times greater than the rest. Bishop et al [2000] reported over 3 million individual‐vehicle remote‐sensing measurements from the Denver area. From those data, we infer that “superemitters” are about 6% of the vehicles and, on average, emit about 17 times the CO of the remainder.…”
Section: Emission Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…An example of a technical project was an Intelligent Transport Systems (ITS) Operational Test project sponsored by the United States Department of Transportation/Federal Highway Administration (USDOT/FHWA), which was designed to support cleaner air by providing real-time tailpipe emissions information to the driving public. The operational test project consisted of the installation of an ITS system (Figure 1) that measured real-time tailpipe carbon monoxide (CO) emissions from passing vehicles, a variable message sign (VMS) that immediately presented the CO emissions levels to the motorists (Figure 2), and auxiliary support information services (Figure 3) such as a hotline and brochures (Bishop et al 2000;Bohren and Williams 1997). The ITS, a remote sensing information system (RSIS), uses a remote sensing device (RSD).…”
Section: E X a M P L E O F P R O J E C T E Va L U At I O Nmentioning
confidence: 99%